1995
DOI: 10.1080/00313029500169452
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria, viruses, yeasts and protozoans associated with diarrheal disease in Singapore

Abstract: Labile toxin producing enterotoxic E. coli (ETEC) were the commonest pathogen isolated from diarrheal stools of hospitalized children (21%) and adults (26%) in Singapore. Salmonellas ranked a close second in children (19%). Other bacterial pathogens were isolated from less than 5% of subjects. Blastocystis hominis was detected in 4.3% of diarrheal stools when a simple sedimentation technique was used. Cryptosporidium was not detected at all. An analysis of yeast counts in smears of diarrheal and non-diarrheal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…However, the rate is comparable to data reported from other countries in the region such as in India where rotavirus accounted for 23.4% of diarrhea hospitalizations [14,15], 24.9% in Bangladesh [16] and is similar to the median proportion of diarrhea hospitalizations estimated for low-income countries (21%) by Parashar et al [17]. Compared to prevalence rates reported in Sri Lanka in the past the present rate shows a similarity to the rate reported by Mertens et al [5] in the district of Kurunegala (21.9%) but is lower than that reported at the Lady Ridgeway Hospital in Colombo (30%) [4]. The age distribution of rotavirus episodes indicated that only a minority of cases occurred during the first two months of life and the peak number of rotavirus gastroenteritis (n = 37) was observed during the second year of life.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the rate is comparable to data reported from other countries in the region such as in India where rotavirus accounted for 23.4% of diarrhea hospitalizations [14,15], 24.9% in Bangladesh [16] and is similar to the median proportion of diarrhea hospitalizations estimated for low-income countries (21%) by Parashar et al [17]. Compared to prevalence rates reported in Sri Lanka in the past the present rate shows a similarity to the rate reported by Mertens et al [5] in the district of Kurunegala (21.9%) but is lower than that reported at the Lady Ridgeway Hospital in Colombo (30%) [4]. The age distribution of rotavirus episodes indicated that only a minority of cases occurred during the first two months of life and the peak number of rotavirus gastroenteritis (n = 37) was observed during the second year of life.…”
Section: Discussionsupporting
confidence: 82%
“…Group A rotaviruses cause the vast majority of human infections and is the focus of vaccination efforts. Reports from the past indicate that rotavirus was an important etiological agent of acute gastroenteritis among the Sri Lankan pediatric population [4,5]. However, there is scant information regarding the current epidemiology of rotavirus in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%
“…Enteric adenoviruses were found in 11/273 (4%) patients with acute diarrhea. Previous studies in developing countries such as in China, Saudi Arabia and Singapore showed that enteric adenovirus was found in 2.5%, 5.3% Rotavirus 132 96 29 15 69 12 69 69 NLV 38 79 32 32 61 16 58 50 Adenovirus 7 100 15 29 57 43 43 43 and 3% of diarrheal patients respectively [22,24,30]. The fact that enteric adenoviruses produced symptoms that were milder than symptoms in patients with rotavirus infection may have resulted in under-reporting, in that the number of children with adenovirus infections seeking hospital attention may have been few in number.…”
Section: Discussionmentioning
confidence: 97%
“…Enteric adenoviruses were found in 11/273 (4%) patients with acute diarrhea. Previous studies in developing countries such as in China, Saudi Arabia and Singapore showed that enteric adenovirus was found in 2.5%, 5.3% and 3% of diarrheal patients respectively [22,24,30]. The fact that enteric adenoviruses produced symptoms that were milder than symptoms in patients with rotavirus infection may have resulted in under‐reporting, in that the number of children with adenovirus infections seeking hospital attention may have been few in number.…”
Section: Discussionmentioning
confidence: 99%